2001
DOI: 10.1101/gad.916701
|View full text |Cite
|
Sign up to set email alerts
|

The hairless gene mutated in congenital hair loss disorders encodes a novel nuclear receptor corepressor

Abstract: The mammalian hairless (hr) gene plays a critical role in the maintenance of hair growth. Although the hr gene has been identified, the biochemical function of its encoded protein (Hr) has remained obscure. Here, we show that Hr functions as a transcriptional corepressor for thyroid hormone receptors (TRs). We find that two independent regions of Hr mediate TR binding and that interaction requires a cluster of hydrophobic residues similar to the binding motifs proposed for nuclear receptor corepressors (N-CoR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 70 publications
2
179
0
3
Order By: Relevance
“…Hairless functions as a nuclear receptor corepressor (Potter et al, 2001). In addition, mouse Jmj protein was shown to be a transcriptional repressor that directly represses cyclin D1 expression (Toyoda et al, 2003).…”
Section: Functions Of Jumonji Family Proteins In Transcription and Chmentioning
confidence: 99%
See 2 more Smart Citations
“…Hairless functions as a nuclear receptor corepressor (Potter et al, 2001). In addition, mouse Jmj protein was shown to be a transcriptional repressor that directly represses cyclin D1 expression (Toyoda et al, 2003).…”
Section: Functions Of Jumonji Family Proteins In Transcription and Chmentioning
confidence: 99%
“…Hairless protein functions as a nuclear receptor corepressor and interacts with multiple nuclear receptors such as thyroid hormone receptor, retinoic acid receptor-related orphan receptor ␣, and vitamin D receptor (Potter et al, 2001;Moraitis et al, 2002;Hsieh et al, 2003). Hairless represses transcriptional activities in the context of these nuclear receptors (Potter et al, 2001;Moraitis et al, 2002;Hsieh et al, 2003).…”
Section: Hairlessmentioning
confidence: 99%
See 1 more Smart Citation
“…Potter et al [13] demonstrated that the Hr protein encoded by the hairless gene functions as a transcriptional corepressor for thyroid hormone receptor (TR). Hr binds to TR and interacts with histone deacetylases.…”
Section: Discussionmentioning
confidence: 99%
“…The gene is highly conserved between men, mice and rats [1,2,6]. The protein codified by this gene is a transcriptional corepressor for thyroid hormone receptors [13]. This gene is highly expressed in the brain and skin [1,4].…”
Section: Introductionmentioning
confidence: 99%